Emerging Markets Integration in Latin America (MILA) Stock market indicators: Chile, Colombia, and Peru - Edmundo R. Lizarzaburu Bola\~nos; Kurt Burneo Farfán; Hamilton Galindo; Luis Berggrun (Journal of Economics, Finance and Administrative Science, 2015)
This study aims to determine the impact of the Latin American Integrated Market (MILA) start-up in the main indicators of the stock markets of the countries that conform it (Chile, Colombia, and Peru). At the end, several indicators were reviewed to measure the impact on profitability, risk, correlation, and trading volume between markets, using indicators such as: annual profitability, standard deviation, correlation coefficient, and trading volume. The sample period runs from November 2008 to August 2013; and involves the three stock markets associated with MILA: Bolsa de Comercio de Santiago (BCS), Bolsa de Valores de Colombia (BVC) y Bolsa de Valores de Lima (BVL). An additional evaluation for further research would consist of the calculation of relevant indicators to corroborate the validity of the effects found in this investigation corresponding to the integration of the stock exchanges of Lima, Santiago and Bogota, after the integration of the Mexican stock exchange that occurred in 2014. – – El presente estudio pretende determinar el impacto del Mercado Integrado Latinoamericano (MILA) en los principales indicadores del mercado de valores de los países que lo conforman (Chile, Colombia y Perú). Al final se revisaron varios indicadores para medir el impacto sobre la rentabilidad, el riesgo, la correlación y el volumen de operaciones entre mercados, por medio de indicadores como rentabilidad anual, desviación estándar, coeficiente de correlación y volumen de operaciones. El periodo de muestra se prolongó de noviembre de 2008 a agosto de 2013, e involucró a los tres mercados de valores asociados con el MILA: la Bolsa de Comercio de Santiago (BCS), la Bolsa de Valores de Colombia (BVC) y la Bolsa de Valores de Lima (BVL). Una nueva evaluación para continuar el estudio podría consistir en el cálculo de los indicadores relevantes para corroborar la validez de los efectos revelados en esta investigación en materia de la integración de las bolsas de valores de Lima, Santiago y Bogotá después de la integración de la Bolsa Mexicana de Valores que tuvo lugar en 2014.
Keywords: G15; 330; MILA; Integration; Risk; Emerging markets; MILA; Integración; Riesgo; Mercados emergentes